EFFECTS OF THE MAIN OPERATING PARAMETERS ON SEED HOLDINGIN A SEEDER-PNEUMATIC METERING DEVICE WITH AN INCLINED PLATE FOR MAIZE - Thiet, Nguyen; Thong, Nguyen (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
Today's pneumatic sowing machines often use a seeder-pneumatic metering device with vertical seed discs. The weakness of a seeder-pneumatic metering device with a vertical disc is its low efficiency in receiving and holding seeds. In order to improve the suction and retention of seeds during sowing, the seed disc in a metering device was placed tilted compared to the vertical direction (pneumatic metering device with an inclined disc). The study was carried out according to the single-factor experimental method to determine the main working parameters of the aerodynamic sowing unit combined with the inclined disc.The results showed that an inclined seed disc is more effective than a vertical one in receiving and holding seeds during the sowing process. Specifically, the research focused on determining the effects of the main parameters - suction pressure, seed hole diameter, seed hole velocity, and angle of the seed disc - on the ability of the metering device to receive and hold seeds. The experimental results showed that an effective maize pneumatic metering device with an inclined disc has the following working parameters: 50-100mmHg vacuum pressure; 4-5.5mm seed hole diameter; a seeding hole velocity of less than 0.68 m/s; and the seed disc angled at 20-35degrees from the vertical direction.